Evaluation of Synthetic and Semi- synthetic Culture Media for Endo-1, 4-β- Glucanases Secretion by Trichoderma koningiopsis. (2015) - Castrillo, M.; Bich, G.; Kramer, G.; Velazquez, J.; Rodriguez, M.; Zapata, P.; Villalba, L.
Abstract: The actual demand of energy and the environmental concerns together with the reduced fossil fuel reserves have played an important role to convert the second generation bioethanol production into an attractive research area. To convert lignocellulosic biomass to bioethanol the cellulosic components must be hydrolyzed to fermentable sugars. Trichoderma fungi secrete large amounts of enzymes of industrial interest such as cellulases, able to degrade holocellulose in the saccharification of lignocellulosic biomass. In this work we evaluated endo-1.4-β-glucanases enzymatic secretion of Trichoderma koningiopsis from Misiones province, in synthetic medium, with carboxymethylcellulose as carbon source; and semi-synthetic medium, with pine sawdust as carbon source. Higher values of endo-1.4-β-glucanases were reached when the semi-synthetic medium was used. It could be concluded that pine sawdust seems to be a good candidate for utilization as carbon source in culture media aiming to obtain good enzyme secretion, being also an economic and easily available substrate.